An intranasal subunit vaccine induces protective systemic and mucosal antibody immunity against respiratory viruses in mouse models - Aina Karen Anthi; Anette Kolderup; Eline Benno Vaage; Malin Bern; Sopisa Benjakul; Elias Tjärnhage; Fulgencio Ruso-Julve; Kjell-Rune Jensen; Heidrun Elisabeth Lode; Marina Vaysburd; Jeannette Nilsen; Marie Leangen Herigstad; et al. (Nature Communications)
Abstract Although vaccines are usually given intramuscularly, the intranasal delivery route may lead to better mucosal protection and limit the spread of respiratory virus while easing administration and improving vaccine acceptance. The challenge, however, is to achieve delivery across the selective epithelial cell barrier. Here we report on a subunit vaccine platform, in which the antigen is genetically fused to albumin to facilitate FcRn-mediated transport across the mucosal barrier in the presence of adjuvant. Intranasal delivery in conventional and transgenic mouse models induces both systemic and mucosal antigen-specific antibody responses that protect against challenge with SARS-CoV-2 or influenza A. When benchmarked against an intramuscularly administered mRNA vaccine or an intranasally administered antigen fused to an alternative carrier of similar size, only the albumin-based intranasal vaccine yields robust mucosal IgA antibody responses. Our results thus suggest that this needle-free, albumin-based vaccine platform may be suited for vaccination against respiratory pathogens.